(untitled) (Jurnal Teknologi (Sciences & Engineering), 2023)
Magnetic and microwave absorption properties of CoxFe(3-x)O4 semi-hard materials (x = 0.75, 1.0, and 1.5) synthesized have been carried out using the chemical method of sol-gel. The mixture of iron nitrate Fe2(NO3)3 and cobalt nitrate Co(NO3)2 dissolved in ethylene glycol, then the mixture was heated while stirring at 60 °C for 1 hour to form a gel. After that dried at a temperature of 120°C for 5 hours. A fine powder of CoxFe(3-x)O4 was obtained through the grinding process. The CoxFe(3-x)O4 powder crystallization was done by sintering at 1000 °C for 5 hours. The X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM), Vibrating-sample magnetometer (VSM), and Vector Network Analyzer (VNA) is used to investigate phase identification, particle morphology, magnetic properties, and microwave absorption ability, respectively. Based on the phase identification show that the samples with composition x = 0.75 have two phases, namely CoFe2O4 and Fe2O3. The sample composition for x ³ 1 is a single phase of CoFe2O4. The particle morphology is homogeneous with spherical and the particle size is about 100 – 500 nm. The samples act ferromagnetic behavior with a saturation magnetization (Ms) of 26.1-40.4 emu/g and coercivity field (Hc) of 223-299 Oe. The maximum reflection loss (RL) value of -14.03 dB at the frequency 10.98 GHz occurred in a single-phase sample with a composition of x = 1.0. This study provided a new composite material with great potential for the development of microwave-absorbing materials.